2005
DOI: 10.1093/rpd/nci755
|View full text |Cite
|
Sign up to set email alerts
|

Entrance radiation doses during paediatric cardiac catheterisations performed for diagnosis or the treatment of congenital heart disease

Abstract: The purpose of this study was to estimate the radiation exposure of children, during cardiac catheterisations for the diagnosis or treatment of congenital heart disease. Radiation doses were estimated for 45 children aged from 1 d to 13 y old. Thermoluminescent dosemeters (TLDs) were used to estimate the posterior entrance dose (DP), the lateral entrance dose (DLAT), the thyroid dose and the gonads dose. A dose-area product (DAP) meter was also attached externally to the tube of the angiographic system and gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The results of this survey show that radiation doses have a very large range (see Table IV), as shown by other pediatric surveys. 7,9,[11][12][13][14][15] However, few papers 4,5,8,10,16 reported radiation dose values by age group, as shown in Table VII. In this summary of the median values of P ka , the values of our survey tend to be lower, probably derived from the awareness of cardiologists in the management of patient doses and the careful setting of the x-ray system for pediatric protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this survey show that radiation doses have a very large range (see Table IV), as shown by other pediatric surveys. 7,9,[11][12][13][14][15] However, few papers 4,5,8,10,16 reported radiation dose values by age group, as shown in Table VII. In this summary of the median values of P ka , the values of our survey tend to be lower, probably derived from the awareness of cardiologists in the management of patient doses and the careful setting of the x-ray system for pediatric protocols.…”
Section: Discussionmentioning
confidence: 99%
“…3 The first step in managing the risks from ionizing radiation is to know the dose values imparted to the patients during the imaging procedures. Several papers have been published on patient dose values for pediatric cardiac procedures, [4][5][6][7][8][9][10][11][12][13][14][15][16] but there has not yet published papers on these procedures in Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…The catheterization procedure is carried out with all precautions to minimize the effects of radiation on the operator and patient, so that the fluoroscopy time is kept as low as possible. 19 The median radiation time was 13.3 minutes in acyanotic patients and 14.3 minutes in cyanotic patients. Kumar et al found that radiation time ranged from 2.4 to 11 minutes in acyanotic patients and 8-28 minutes in cyanotic patients.…”
Section: Discussionmentioning
confidence: 95%
“…Even though the long-term risks of fatal malignancy following a single pediatric catheter investigation seems very low, the effect of repetitive exposure is unclear [7], [31]. In general, DAP values measured during pediatric catheterizations show an excellent correlation with the entrance radiation dose and skin doses measured with thermoluminescent dosemeters (TLDs) or can be transferred by calculation models to effective doses and are therefore valid to obtain a real-time measurement of the total amount of radiation used [4], [13], [32], [33], [34], [35]. Similar results are obtained when calculating effective doses from DAP as published by the International Commission on Radiology Protection and measuring the effects on DNA damage [8].…”
Section: Discussionmentioning
confidence: 99%